2014
DOI: 10.5114/kitp.2014.41928
|View full text |Cite
|
Sign up to set email alerts
|

Percentages of NKT cells in the tissues of patients with non-small cell lung cancer who underwent surgical treatment

Abstract: IntroductionNatural killer T (NKT) cells are involved in the antitumor response by direct cytotoxicity and indirectly through activation of effector cells. Recent studies have shown a relationship between the number and function of NKT cells and clinical outcomes. NKT cells seem to represent a promising tool for immunotherapy of cancer.The aim of the studyThe aim of the study was to evaluate the distribution of NKT cells in peripheral blood, lymph nodes and tumor tissue of non-small cell lung cancer (NSCLC) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In agreement with the beneficial role of i NKT cells in lung cancer, the numbers of i NKT cells were compared following the cancers of differing histologic type and stage. It was found that the number was: (1) lower in adenocarcinoma, which has the worse prognosis than in squamous cell carcinoma ( 157 ); (2) lower in stage 1 than in stage IV cancers ( 156 ). Another human study showed that the percentage of Vα24 NKT cells in the PBMC of lung cancer patients was 0.01–0.03%; however, patients with recurrent cancers harbored a significantly lower percentage of NKT cells than healthy donors ( 158 ).…”
Section: Lipid-reactive T Cells In Pulmonary Disordersmentioning
confidence: 99%
“…In agreement with the beneficial role of i NKT cells in lung cancer, the numbers of i NKT cells were compared following the cancers of differing histologic type and stage. It was found that the number was: (1) lower in adenocarcinoma, which has the worse prognosis than in squamous cell carcinoma ( 157 ); (2) lower in stage 1 than in stage IV cancers ( 156 ). Another human study showed that the percentage of Vα24 NKT cells in the PBMC of lung cancer patients was 0.01–0.03%; however, patients with recurrent cancers harbored a significantly lower percentage of NKT cells than healthy donors ( 158 ).…”
Section: Lipid-reactive T Cells In Pulmonary Disordersmentioning
confidence: 99%